Mouse pancreatic tumor organoids reveal synergistic efficacy of low-dose anticancer drug and radiation combinations - Keepers, Zachery; Sharma, Aniketh; Roy, Sanjit; Ryan, Hurley; Bhandary, Binny; Ren, Lei; Lamichhane, Narottam; Shukla, Hem D. (Frontiers in Medicine, 2025)
BackgroundPancreatic cancer is the fourth-leading cause of cancer death in the United States, with a 5-year survival rate of only 13%. Most patients with locally advanced pancreatic cancer receive chemotherapy with or without radiation therapy (RT). However, current treatment approaches often result in limited clinical response, highlighting the need for novel therapeutic strategies tested in robust model systems. Pancreas tumor-derived organoids offer a promising representative preclinical model for assessing responses to chemotherapy drugs, RT, and combination treatments.MethodsPancreatic tumor organoids (PTOs) were derived from Panc02 mouse flank tumors. The PTO microenvironment was characterized and compared with the in vivo tumor using immunohistochemical and immunofluorescence staining for alpha-smooth muscle actin (α-SMA) and vimentin. The organoids were treated with fractionated x-ray radiation, gemcitabine, 5-fluorouracil (5-FU), and combinations of drugs with radiation. Treatment response was observed and quantified using brightfield imaging and immunofluorescence to detect reactive oxygen species (ROS) and γH2AX.ResultsThree-dimensional PTOs exhibited expression patterns of α-SMA and vimentin similar to in vivo tumors, underscoring their relevance as a translational preclinical model. Dose-dependent growth suppression was observed following treatment with individual chemotherapy agents and radiation. Combination treatments with low-dose chemotherapy and radiation resulted in significantly greater inhibition of organoid growth compared to single-modality treatments. This enhanced effect was validated by reduced vimentin expression, increased γH2AX expression, and elevated reactive oxygen species (ROS) production, indicating amplified DNA damage and cytotoxicity.ConclusionCombining low-dose chemotherapy with radiation is significantly more effective at inhibiting pancreatic tumor organoid growth than either treatment alone, likely by targeting distinct signaling pathways. Additionally, the tumor organoid model holds promise for examining drug and radiation treatment responses, with potential for translational impact.